Hubungan Perbedaan Beban Trauma Dengan Gambaran Histopatologi Edema Sel Otak Tikus Pasca Cedera Otak Traumatik: The Relationship between Trauma Load Differences and Histopathological Description of Rat Brain Cell Edema Post Traumatic Brain Injury - Bayu Putra Wibowo; Rohadi Rohadi; Lale Maulin Prihatina; Zikrul Haikal (LPPM Universitas Mataram, 2023)
Traumatic brain injury is a condition of the head structure that is impacted or traumatized, causing disruption of brain function. This condition is one of the types of injuries that have the most severe effects on disability and death. Globally, 60 million people suffer from traumatic brain injury each year, with the most common complication being intracranial hemorrhage which increases the risk of death and disability. The incidence of traumatic brain injury is most common in the age group of children (0 - 4 years), adolescents and young adults (15-24 years) and the elderly (> 65 years). Where the most common causes are falls and vehicle accidents. This study aims to determine the histopathological description of edema in rat brain cells after traumatic brain injury and to analyze the relationship between differences in trauma burden and histopathological features of brain cell edema in rats after traumatic brain injury. This research is an experimental conducted by giving treatment to the object under study and then observing it. Sampling in this research will use purposive sampling. Where the researcher has determined the criteria of the sample to be used in the study so that it can represent the population. Based on the research conducted, it was found that there was a relationship between differences in trauma load and the percentage of brain cell edema in rats after experiencing traumatic brain injury. Where the greater the load given, the wider the surface of the brain that is experiencing edema. The results showed a significant edema appearance compared to the histopathological appearance of rat brain cells in normal samples. In addition, it was found that there was an increase in the percentage of areas with edema with a greater trauma load p=0.8156.